Regulation of Microglial Functions by Purinergic Mechanisms in the Healthy and Diseased CNS - Peter Illes; Patrizia Rubini; Henning Ulrich; Yafei Zhao; Yong Tang (Cells, 2020)
Microglial cells, the resident macrophages of the central nervous system (CNS), exist in a process-bearing, ramified/surveying phenotype under resting conditions. Upon activation by cell-damaging factors, they get transformed into an amoeboid phenotype releasing various cell products including pro-inflammatory cytokines, chemokines, proteases, reactive oxygen/nitrogen species, and the excytotoxic ATP and glutamate. In addition, they engulf pathogenic bacteria or cell debris and phagocytose them. However, already resting/surveying microglia have a number of important physiological functions in the CNS; for example, they shield small disruptions of the blood–brain barrier by their processes, dynamically interact with synaptic structures, and clear surplus synapses during development. In neurodegenerative illnesses, they aggravate the original disease by a microglia-based compulsory neuroinflammatory reaction. Therefore, the blockade of this reaction improves the outcome of Alzheimer’s Disease, Parkinson’s Disease, multiple sclerosis, amyotrophic lateral sclerosis, etc. The function of microglia is regulated by a whole array of purinergic receptors classified as P2Y12, P2Y6, P2Y4, P2X4, P2X7, A2A, and A3, as targets of endogenous ATP, ADP, or adenosine. ATP is sequentially degraded by the ecto-nucleotidases and 5′-nucleotidase enzymes to the almost inactive inosine as an end product. The appropriate selective agonists/antagonists for purinergic receptors as well as the respective enzyme inhibitors may profoundly interfere with microglial functions and reconstitute the homeostasis of the CNS disturbed by neuroinflammation.